2023
DOI: 10.2196/48920
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Virtual Consultations on the Quality of Primary Care: Systematic Review

Kate Campbell,
Geva Greenfield,
Edmond Li
et al.

Abstract: Background The adoption of virtual consultations, catalyzed by the COVID-19 pandemic, has transformed the delivery of primary care services. Owing to their rapid global proliferation, there is a need to comprehensively evaluate the impact of virtual consultations on all aspects of care quality. Objective This study aims to evaluate the impact of virtual consultations on the quality of primary care. Methods A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Health outcomes in patients who saw doctors remotely at least matched in-person care outcomes for mental illness, alcohol misuse, weight management, and advice on quitting smoking, showed a review of previous research involving more than 5.4 million patients around the world. Reported in the Journal of Medical Internet Research ,1 the study also found some evidence that remote consultations saved time for doctors, reduced waiting times, and were seen as more convenient but also that patients who were seen virtually felt less well supported in making informed choices.…”
Section: General Practicementioning
confidence: 81%
“…Health outcomes in patients who saw doctors remotely at least matched in-person care outcomes for mental illness, alcohol misuse, weight management, and advice on quitting smoking, showed a review of previous research involving more than 5.4 million patients around the world. Reported in the Journal of Medical Internet Research ,1 the study also found some evidence that remote consultations saved time for doctors, reduced waiting times, and were seen as more convenient but also that patients who were seen virtually felt less well supported in making informed choices.…”
Section: General Practicementioning
confidence: 81%
“…The primary care landscape has undergone an intense transformation since early 2020, further hastened by advancements in digital technologies expedited by the COVID-19 pandemic 1 2. Specifically, virtual consultations ( ie, remote synchronous consultations performed using telephone or online conferencing software) emerged as an innovative approach to patient–provider interaction, with the potential to transform care delivery by improving effectiveness and timeliness of care 3…”
Section: Introductionmentioning
confidence: 99%
“…1 2 Specifically, virtual consultations ( ie, remote synchronous consultations performed using telephone or online conferencing software) emerged as an innovative approach to patient–provider interaction, with the potential to transform care delivery by improving effectiveness and timeliness of care. 3 …”
Section: Introductionmentioning
confidence: 99%